2013
DOI: 10.1186/1471-2288-13-79
|View full text |Cite
|
Sign up to set email alerts
|

ClinicalTrials.gov registration can supplement information in abstracts for systematic reviews: a comparison study

Abstract: BackgroundThe inclusion of randomized controlled trials (RCTs) reported in conference abstracts in systematic reviews is controversial, partly because study design information and risk of bias is often not fully reported in the abstract. The Association for Research in Vision and Ophthalmology (ARVO) requires trial registration of abstracts submitted for their annual conference as of 2007. Our goal was to assess the feasibility of obtaining study design information critical to systematic reviews, but not typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…8 A previous evaluation of the content of abstracts of randomized trials presented at the ARVO Annual Meeting also found important study design information frequently unreported. 9 However, the authors concluded that missing information was often available in the corresponding ClinicalTrials.gov record. Because diagnostic accuracy studies are rarely registered, 10 complete reporting of conference abstracts is even more critical for these studies.…”
Section: Discussionmentioning
confidence: 99%
“…8 A previous evaluation of the content of abstracts of randomized trials presented at the ARVO Annual Meeting also found important study design information frequently unreported. 9 However, the authors concluded that missing information was often available in the corresponding ClinicalTrials.gov record. Because diagnostic accuracy studies are rarely registered, 10 complete reporting of conference abstracts is even more critical for these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of conference abstracts in this searchable database means searching for conference abstracts is less resourceintensive than in the past. Second, largely driven by their brevity, abstracts may not contain adequate information for systematic reviewers to appraise the design, methods, risk of bias, outcomes, and results of studies reported in the abstracts [18][19][20][21]. Third, the dependability of results presented in abstracts also is questionable [22][23][24], which occurs at least in part because (1) most abstracts are not peer-reviewed and (2) results reported in abstracts are often preliminary and/or based on limited analyses conducted in a rush to meet conference deadlines.…”
Section: Arguments Against Including Conference Abstracts In Systematmentioning
confidence: 99%
“…Conversely, the limited information on study design in abstracts makes it difficult to evaluate the validity of study methodology and results, although minimized if CON-SORT guidelines for conference abstract reporting are adopted [31].…”
Section: Level Of Evidencementioning
confidence: 99%